DESAIN DAN PENGEMBANGAN SISTEM INFORMASI BERBASIS WEBSITE UNTUK PROMOSI PRODUK UNGGULAN UMKM DI TULANG BAWANG BARAT - Hafidh Arsala Huda, Muhammad; Zulkarnaini, Zulkarnaini; Meiliza, Meiliza; Aglasia, Adimas (Jurnal SIMADA (Sistem Informasi dan Manajemen Basis Data), 2024)
MSMEs or micro small and medium enterprises is a productive business entity that operates independently and can be owned by individuals or companies in all economic sectors in west tulang bawang MSMEs has not fully utilized web technology for online promotion and ordering currently the sale of MSMEs products is still done traditionally and data recording is still done manually in books which has the potential to cause loss damage or data manipulation to overcome this problem the rapid application development method is used with UML tools such as use case diagrams activity class and sequence the database used is MySQL the result of this research is an online sales and ordering system that allows MSMEs owners to manage product data confirm orders and print reports the admin part can see sales data and reports while consumers can make order transactions up to payment